Case report: Effective treatment of rituximab-resistant minimal change disease with obinutuzumab in an adult - Wang, Qiang; Lin, Lin; Zhen, Junhui; Jiang, Bei; Liu, Guangyi (Frontiers in Immunology, 2024)
Background: Minimal change disease (MCD) is a common cause of adult nephrotic syndrome. Most adults with MCD achieve a complete remission (CR) after initial steroid therapy. However, approximately 30% of adults who respond to steroids experience frequent relapses, becoming steroid dependent, and potentially developing refractory MCD. Treating refractory MCD in adults poses a significant challenge. Main body: A 37-year-old woman presented to the nephrology department with a 6-year history of MCD. The diagnosis of MCD was confirmed via renal biopsy. She initially achieved CR with steroid treatment but experienced relapse during steroid tapering. Subsequent CR was achieved with a regimen of steroids and tacrolimus although multiple relapses occurred. Rituximab led to another CR, but its maintenance lasted only 6 months. The response to subsequent rituximab treatments was unsatisfactory. Ultimately, obinutuzumab was selected, resulting in the induction and maintenance of CR for 12 months. Conclusions: This case demonstrates the successful treatment of frequently relapsed, steroid-dependent, and rituximab-resistant MCD with obinutuzumab. Obinutuzumab is as a promising therapeutic option for rituximab-resistant MCD.